The influence of the hydrophobic component content on the properties of hybrid polymer-inorganic membranes - Demydova, Khrystyna; Horechyy, Andriy; Yevchuk, Iryna; Demchyna, Oksana (Lviv Politechnic Publishing House, 2018)
УФ-затвердженням суміші акрилатних мономерів з одночасним формуванням неорганічної сітки внас- лідок золь-гель перетворення тетраетоксисилану синтезовано гібридні полімер-неорганічні мембрани з різним складом полімерної матриці. Склад полімерної складової варіювався зміною співвідношення гідрофільного і гідрофобного моно- мерів, у той час як вміст неорганічної складової залишався по- стійним. Досліджено морфологію, термічну поведінку та водопоглинання синтезованих мембран.

Hybrid polymer-inorganic membranes with varied composition of polymeric matrix were synthesized by UV-curing of a mixture of acrylic monomers with simultaneous formation of inorganic network via sol-gel reaction of tetraethoxysilane. Composition of polymeric counterpart was varied by changing the ratio of hydrophilic and hydrophobic monomers, whereas the content of inorganic counterpart was maintained constant. Morphology, thermal behavior and water uptake of membranes were investigated.
Вплив вмісту гідрофобного компоненту на властивості гібридних полімер-неорганічних мембран
Keywords: полімер-неорганічна мембрана; УФ-за- твердження; золь-гель процес; акрилат; тетраетоксисилан; polymer-inorganic membrane; UV-curing; sol-gel process; acrylate; tetraethoxysilane